'It's about willpower in the end. You've got to keep going': a qualitative study exploring the experience of pain in inflammatory bowel disease. Issue 4 (November 2019) - Sweeney, Louise; Moss-Morris, Rona; Czuber-Dochan, Wladyslawa; Belotti, Laure; Kabeli, Zoe; Norton, Christine
Background: Pain is a widely experienced symptom of inflammatory bowel disease (IBD), which has significant psychological and functional impacts on patients. Understanding the aetiology and management of chronic pain is a poorly understood area of IBD research. This qualitative study aimed to explore the experiences of individuals with IBD and pain, the pain management strategies they use and any needs for future pain management interventions. Methods: In all, 14 individuals with IBD were purposively recruited and interviewed (face-to-face or telephone) using a topic guide. Interviews were transcribed and analysed using inductive thematic analysis. Results: Themes identified were 'vicious cycles', 'findings solutions' and 'attitudes'. The experience and impact of pain were rarely viewed in isolation, but rather within the context of a cycle of IBD symptoms. Other 'vicious cycles' identified included anxiety, avoidance and inactivity, and poor understanding and communication. Pain management included short- and long-term strategies. Searching for a solution for pain had an emotional impact on individuals. There were contrasting attitudes from participants, including defeat, tolerance and acceptance. Conclusion: This study provides an understanding of the experience of pain in IBD. The interaction of pain with accompanying IBD symptoms has an emotional and physical impact on individuals, and creates a barrier to adequate assessment, understanding and treatment of pain. Patients rely on their own experiences, and a trial and error approach to apply helpful strategies. Adjuvant behavioural therapies may be beneficial for patients experiencing pain and psychological distress, and to facilitate self-management.